2017
DOI: 10.7196/samj.2017.v107i10.11371
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement in prevention of mother-to-child transmission of HIV in the context of partner testing in Goba town, Ethiopia: A facility-based cross-sectional study

Abstract: Background. Antenatal care (ANC) is an entry point for the prevention of mother-to-child transmission (PMTCT), particularly when a man accompanies his spouse for voluntary counselling and testing (VCT), even though this seldom happens in Ethiopia. Objective. To study the role of male partners in improving PMTCT/ANC, which is essential to prevent HIV/AIDS transmission in this country. Our study focused on identifying barriers for the low involvement in PMTCT/ANC among male partners whose spouses received ANC. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 4 publications
9
8
0
Order By: Relevance
“…Husbands who had attended secondary and above education were 1.93 times more likely to accompany their wives in ANC than those who had no formal education. Similar studies in Nepal, Central Ghana and Goba town Ethiopia have found that education level is an important factor for husband antenatal care attendance [14,18,29]. This may be related to as people more educated they could easily understood the importance of husband attendance in maternal health care service including antenatal care.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Husbands who had attended secondary and above education were 1.93 times more likely to accompany their wives in ANC than those who had no formal education. Similar studies in Nepal, Central Ghana and Goba town Ethiopia have found that education level is an important factor for husband antenatal care attendance [14,18,29]. This may be related to as people more educated they could easily understood the importance of husband attendance in maternal health care service including antenatal care.…”
Section: Discussionsupporting
confidence: 56%
“…For instance a study which was conducted in Nepal is 39% [14]. In sub-Saharan Africa, husband antenatal care attendance varies between 12.5%-18.7% [17] and in Ethiopia studies showed that husband antenatal care attendance is rage from 19.7 22.7% [18][19][20]. Husband ANC attendance program still remains low in developing countries including Ethiopia [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“… 15 The less partner HIV test in this study was attributed to being busy, which is the same as the study found in Goba. 16 Another reason attributed to men not being tested was proxy testing the finding is congruent with that of the study done by Goba in Ethiopia. 16 But compared to the study that was made in Addis Ababa it is higher which shows 44% reported having been tested during the partner’s pregnancy.…”
Section: Discussionsupporting
confidence: 74%
“…This finding is higher than to study conducted in Goba and Gondar town which was 22.7% and 40.1%, respectively. 16 , 17 The possible reasons for this might be the easily accessibility of transportation to reach health facilities. However, this study is lower than finding in a survey conducted by Abraham Haileamlak in Ethiopia (72%), 26 a study conducted in Rwanda which was 81% of the male partners being tested 5 and also a study conducted in Uganda revealed that the majority (more than 90%) of male partners who attended the antenatal clinic accepted HIV counseling and testing for HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation